Tracking neuronal marker expression inside living differentiating cells using molecular beacons - Ilieva, Mirolyuba; Vedova, Paolo D.; Hansen, Ole; Dufva, Martin (Frontiers in Cellular Neuroscience, 2013)
Monitoring gene expression is an important tool for elucidating mechanisms of cellular function. In order to monitor gene expression during nerve cell development, molecular beacon (MB) probes targeting markers representing different stages of neuronal differentiation were designed and synthesized as 2’-O-methyl RNA backbone oligonucleotides. MBs were transfected into human mesencephalic cells (LUHMES) using streptolysin-O-based membrane permeabilization. Mathematical modeling, simulations and experiments indicated that MB concentration was equal to the MB in the transfection medium after 10 minutes transfection. The cells will then each contain about 60 000 MBs. Gene expression was detected at different time points using fluorescence microscopy. Nestin and NeuN mRNA were expressed in approximately 35% of the LUHMES cells grown in growth medium, and in 80-90% of cells after differentiation. MAP2 and tyrosine hydroxylase mRNAs were expressed two and three days post induction of differentiation respectively. Oct 4 was not detected with MB in these cells and signal was not increased over time suggesting that MB are generally stable inside the cells. The gene expression changes measured using MBs were confirmed using qRT-PCR. These results suggest that MBs are simple to use sensors inside living cell, and particularly useful for studying dynamic gene expression in heterogeneous cell populations.